Fa’āliyyah Barnāmaj Ma’rifī Sulūkī li Khafđi Mustawiyāt al-Kurtizūl Lada Țālibāti al-Śaffi al-Śānī ‘Asyar: فاعلية برنامج معرفي سلوكي لخفض مستويات الكورتيزول لدى طالبات الصف الثاني عشر - Omer, Bareen Sherwan; Naamat, Arian Tatar (Study Program of Arabic Language Teaching, 2025)
The aim of the current research is to examine the effectiveness of a cognitive-behavioral program in reducing cortisol levels among 12th-grade science stream female students. The researchers adopted the experimental method, as it is appropriate for the topic of the research. The study sample consisted of 60 female students from secondary schools in the Faida area, Dohuk Governorate. The sample was divided into two groups: an experimental group of 30 students who underwent the cognitive-behavioral program, and a control group of 30 students who did not receive any intervention during the implementation of the program. The participants were selected using a purposive sampling method. To achieve the research objective, the researchers formulated two main hypotheses: first, there is no statistically significant difference at the (0.05) level between the mean scores of cortisol level reduction in the experimental and control groups, and second, there is no statistically significant difference at the (0.05) level between the pre-test and post-test scores in reducing cortisol levels among the experimental group. The study relied on salivary cortisol measurements to assess psychological stress levels, and the cognitive-behavioral program was prepared by the researchers. The psychometric properties of the biological measurements (validity, reliability, measurement accuracy, result reliability) were established. The measurements were then applied, and data were collected and analyzed statistically using the Statistical Package for the Social Sciences (SPSS). The research concluded that there is a significant difference between the mean scores of the experimental and control groups in favor of the experimental group in reducing cortisol levels. The results also showed a statistically significant difference between the pre-test and post-test scores of the experimental group in favor of the post-test in terms of reducing cortisol levels.